2019
DOI: 10.1038/s41598-019-39327-7
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Morphology of Cortical Terminals in the Cat Thalamus from the Anterior Ectosylvian Sulcus

Abstract: Two main types of cortical terminals have been identified in the cat thalamus. Large (type II) have been proposed to drive the response properties of thalamic cells while smaller (type I) are believed to modulate those properties. Among the cat’s visual cortical areas, the anterior ectosylvian visual area (AEV) is considered as one of the highest areas in the hierarchical organization of the visual system. Whereas the connections from the AEV to the thalamus have been recognized, their nature (type I or II) is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 63 publications
1
21
0
Order By: Relevance
“…Our findings corroborate these results showing that labeled neurons in Area 17 were almost exclusively located in Layer 5. Interestingly, the present study and our previous ones (Abbas Farishta et al, 2020; Huppé‐Gourgues et al, 2006, 2019) demonstrated that despite the large number of Layer 5 inputs from Area 17, there is still some contribution from Layer 6 neurons.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…Our findings corroborate these results showing that labeled neurons in Area 17 were almost exclusively located in Layer 5. Interestingly, the present study and our previous ones (Abbas Farishta et al, 2020; Huppé‐Gourgues et al, 2006, 2019) demonstrated that despite the large number of Layer 5 inputs from Area 17, there is still some contribution from Layer 6 neurons.…”
Section: Discussionsupporting
confidence: 64%
“…In cats, CT projections from Area 17 in LPl are mostly of Type II with few Type I axons (Abbas Farishta et al, 2020; Guillery et al, 2001; Huppé‐Gourgues et al, 2006; Ojima et al, 1996). Three previous studies from our group characterized the CT terminals from areas 17, 21a, PMLS, and AEV in the cat LP (Abbas Farishta et al, 2020; Huppé‐Gourgues et al, 2006, 2019). These studies revealed a clear distinction between the CT projections from Area 17 and the extrastriate areas PMLS, 21a, and AEV.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations